2017
DOI: 10.1038/s41598-017-10940-8
|View full text |Cite
|
Sign up to set email alerts
|

Armored CAR T cells enhance antitumor efficacy and overcome the tumor microenvironment

Abstract: Chimeric antigen receptor (CAR) T cell therapy has shown limited efficacy for the management of solid tumor malignancies. In ovarian cancer, this is in part due to an immunosuppressive cytokine and cellular tumor microenvironment which suppresses adoptively transferred T cells. We engineered an armored CAR T cell capable of constitutive secretion of IL-12, and delineate the mechanisms via which these CAR T cells overcome a hostile tumor microenvironment. In this report, we demonstrate enhanced proliferation, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
234
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 321 publications
(251 citation statements)
references
References 52 publications
1
234
0
Order By: Relevance
“…As macrophage depletion by clodronate treatment significantly prolongs overall survival of tumour‐bearing mice treated with the IL‐12‐expressing CAR‐T cells, these results suggest that co‐expression of IL‐12 intensifies the therapeutic potential of CAR‐T cells by depletion of TAM in addition to the augmentation of CAR‐T‐cell cytotoxic capacity (Fig. c) . Although IL‐12 armoured CAR‐T cells deplete TAM via an indirect mechanism, it is suggested that genetic manipulation of T cells to express TAM‐specific CAR can directly eliminate TAM in the tumours.…”
Section: Tam Targeting For Adoptive Ctl Transfer Therapymentioning
confidence: 89%
See 1 more Smart Citation
“…As macrophage depletion by clodronate treatment significantly prolongs overall survival of tumour‐bearing mice treated with the IL‐12‐expressing CAR‐T cells, these results suggest that co‐expression of IL‐12 intensifies the therapeutic potential of CAR‐T cells by depletion of TAM in addition to the augmentation of CAR‐T‐cell cytotoxic capacity (Fig. c) . Although IL‐12 armoured CAR‐T cells deplete TAM via an indirect mechanism, it is suggested that genetic manipulation of T cells to express TAM‐specific CAR can directly eliminate TAM in the tumours.…”
Section: Tam Targeting For Adoptive Ctl Transfer Therapymentioning
confidence: 89%
“…c) . Although IL‐12 armoured CAR‐T cells deplete TAM via an indirect mechanism, it is suggested that genetic manipulation of T cells to express TAM‐specific CAR can directly eliminate TAM in the tumours. In the ID8 ovarian cancer model, TAM in peritoneal tumour ascites expresses a high level of folate receptor β (FR β ) and adoptive transfer of FR β ‐specific CAR‐T cells into the tumour‐bearing mice results in destruction of TAMs and delayed tumour growth (Fig.…”
Section: Tam Targeting For Adoptive Ctl Transfer Therapymentioning
confidence: 99%
“…Armoured CAR T cells that constitutively secrete pro-inflammatory cytokines as a mechanism to overcome local immunosuppression are a novel concept. Similarly, incorporation of immune-checkpoint inhibition into CAR T cell-based strategies, by various combinatorial or built-in approaches, might improve responses 98 ; the findings of several preclinical studies support the effectiveness of this approach, warranting further clinical translation 98,152,159,160 .…”
Section: Car T Cell Strategies Beyond B Cell Targeting Cd19mentioning
confidence: 92%
“…[105][106][107][108][109][110] Accordingly, RCD can no longer be perceived as immunogenic when: (1) the intracellular stress responses regulating the emission of ICD-associated DAMPs are pharmacologically or genetically ablated in cancer cells; or (2) when the molecular machinery dedicated to DAMP detection is inhibited or ablated. 13,44,84,91,93,97 Moreover, ICD-driven immunity can no longer operate in the presence of general immunological defects, 111 such as (1) an intrinsically low antigenicity of cancer cells, owing to low levels of TAAs or downregulation of MHC Class I molecules [112][113][114][115][116][117][118][119] ; (2) an increased immunological tolerance of the host, secondary to increased amounts of immunosuppressive cytokines, [120][121][122][123][124][125][126][127][128] or inhibitors of chemotaxis, [129][130][131][132][133][134] increased tumor infiltration by immunosuppressive cell populations, [135][136][137][138][139][140]…”
Section: Introductionmentioning
confidence: 99%